2012
DOI: 10.1093/infdis/jis682
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 33 Mediates Type 2 Immunity and Inflammation in the Central Nervous System of Mice Infected With Angiostrongylus cantonensis

Abstract: Angiostrongylus cantonensis can induce central nervous system (CNS) injury and cause human eosinophilic meningitis. The CNS has been found to have high expression of interleukin 33 (IL-33), which promotes the pathogenesis of T-helper 2 (Th2)-related disease. Given the predominantly type 2 response induced by A. cantonensis-infected mice and human, it is likely that IL-33 may play a role in aiding this process. We report here that IL-33 protein and ST2L messenger RNA (mRNA) transcripts in the brains were upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Finally, IL-33 and ST2 are overexpressed in the brain in mice infected with Angiostrongylus cantonensis (80,81). In this model, splenocytes and mononuclear brain cells responded to IL-33 through production of IL-5 and IL-13, both of which contribute to eosinophilic meningitis induced by A. cantonensis (80,81).…”
Section: Role Of Il-33/st2 In Helminth Diseasesmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, IL-33 and ST2 are overexpressed in the brain in mice infected with Angiostrongylus cantonensis (80,81). In this model, splenocytes and mononuclear brain cells responded to IL-33 through production of IL-5 and IL-13, both of which contribute to eosinophilic meningitis induced by A. cantonensis (80,81).…”
Section: Role Of Il-33/st2 In Helminth Diseasesmentioning
confidence: 90%
“…Finally, IL-33 and ST2 are overexpressed in the brain in mice infected with Angiostrongylus cantonensis (80,81). In this model, splenocytes and mononuclear brain cells responded to IL-33 through production of IL-5 and IL-13, both of which contribute to eosinophilic meningitis induced by A. cantonensis (80,81). The injection of a monoclonal anti-ST2 antibody 3 days postinfection with further injections every 5 days led to a significant reduction of IL-5 blood levels and of eosinophil influx in the meninges (82).…”
Section: Role Of Il-33/st2 In Helminth Diseasesmentioning
confidence: 97%
“…Conversely, IL-33 mediates pathogenic eosinophilic responses in Angiostrongylus cantonensis infection-induced meningitis, and antibodies against ST2 or IL-33 blockade reduce disease severity [66][67][68]. In the model of experimental autoimmune encephalomyelitis (EAE), IL-33 blockade mediates both pathogenic and protective roles [69][70][71].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…T-cell populations, cytokines, immunoglobulins, matrix metalloprotienases and eosinophils are important components in the host cellular response to infection with A. cantonensis 89 . Peng et al 90 showed that Interleukin 33 mediates type 2 immunity and is involved in causing inflammation in the CNS of mice infected with A. cantonensis. Type 2 immunity is characterized by the induction of CD4 + T helper (TH) 2 cells, which secrete cytokines such as interleukin-4 (IL-4), IL-5, IL-9, and IL-13 causing the inflammatory response 91 .…”
Section: Pathogenesismentioning
confidence: 99%